Evaluation of secondary and micronutrients in Kansas - Gutierrez Rodriguez, Miriam Nicole (Kansas State University, 2016)
The limitation of an essential nutrient for plant growth can affect crop yield. Research has been focused mainly on macronutrients, nevertheless micronutrients are equally important. This thesis is divided into three studies, which had the purpose of assessing frequent questions that producers have about micronutrient fertilizers and their effect on several crops in Kansas. The objective of the first study was to summarize and analyze results from studies since 1962 until 2015 to verify responses to zinc (Zn) and sulfur (S) fertilization in corn (Zea mays), sorghum (Sorghum bicolor (L.) Moench), wheat (Triticum aestivum) and soybean (Glycine max (L.) Merr). The treatments evaluated consisted of fertilizer Zn or S application versus their respective unfertilized treatments. Zinc fertilization significantly increased corn yield; no significant response was found for sorghum, wheat and soybean. Sulfur fertilization did not increase yields on corn and wheat. The objectives of the second study were: (i) to evaluate soybean response to S and micronutrients boron (B), copper (Cu), manganese (Mn), and Zn fertilizer application and to assess soil test and soybean seed and tissue nutrient concentration with fertilization. Treatments consisted of an unfertilized control, micronutrient fertilizer as individual nutrient for B, Cu, Mn, S and Zn applied broadcast pre-plant, in addition to a blend of these nutrients using two different placements (broadcast and band). Secondary and micronutrient fertilization showed no significant effect on soybean yield at any of the ten locations. Zinc fertilization showed significant effects on soybean tissue and seed Zn concentration. The objective of the third study was to evaluate soybean tissue nutrient response to micronutrient fertilizers in field strips with high variability in soil properties in the area evaluated. The study consisted of two strips (with and without fertilizer) and replicated three times. The treatment with fertilizer included a blend of Cu, Mn and Zn at a rate of 11.2 kg ha⁻¹ and B at a rate of 2.8 kg ha⁻¹. Initial soil tests B, Cu, Mn and Zn were not good indicators of soybean tissue response. Within-field variability of soybean Zn and B tissue content were affected by soil pH and organic matter; and these factors may be used to help explain field variability in plant availability. The micronutrient blend treatment showed higher tissue Zn and B values compared to the control. When pH ranged from 5.5 to 7.6, B in soybean tissue was higher on the control than the micronutrient blend treatment. Copper concentration in soybean tissue did not show significant difference between treatments at any location, regardless of pH and organic matter levels.
Keywords: Boron; Copper; Manganese; Soil; Fertilizers; Micronutrients; Sulfur; Agronomic biofortificationSoybean; Zinc